2019
DOI: 10.21475/ajcs.19.13.07.p1644
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nitrate reductase activity (NR) in foliar and radicular tissues of Physalis angulata L.: diurnal variations and protocol optimization

Abstract: Nitrate reductase (NR) is the first enzyme in the nitrogen assimilation pathway. The determination of its activity requires modifications for each plant species. The goal of this work was to evaluate the variation of NR activity throughout the day and the optimization of assay conditions in foliar and radicular tissues of Physalis angulata. The analysis was done in plants cultivated in a hydroponic system at two months of age. The NR activity was based on the in vivo assay method. Enzyme activity was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Segundo observado por Tanan et al, (2019), a presença de nitrato é o gatilho inicial para a produção da redutase do nitrato. Quando não há nitrato, o RNA mensageiro responsável pela fabricação dessa enzima não se acumula, resultando em pouca ou nenhuma atividade da redutase do nitrato.…”
Section: Resultsunclassified
“…Segundo observado por Tanan et al, (2019), a presença de nitrato é o gatilho inicial para a produção da redutase do nitrato. Quando não há nitrato, o RNA mensageiro responsável pela fabricação dessa enzima não se acumula, resultando em pouca ou nenhuma atividade da redutase do nitrato.…”
Section: Resultsunclassified
“…3C). Optimization of NRA at a pH close to neutrality tending to a slight alkalinity has been demonstrated for several species, such as wheat [Brunetti and Hageman, 1976], coffee [Meguro and Magalhães, 1982], soybean [Crafts-Brandner and Harper, 1982], barley [Lillo, 1983], apple tree [Lee and Titus, 1992], pineapple [Nievola and Mercier, 2001], Brachiaria [Cazetta and Villela, 2004], peach palm [Oliveira et al, 2005], sugar cane [Santos et al, 2014], and Physalis angulata L. [Tanan et al, 2019], among others. The effect of pH on NRA has been associated with its influence on the distribution of charges at an active site, which changes the structural conformation of the enzyme [Nelson and Cox, 2018], or changes the rate of nitrate and nitrite translocation across the cell membrane [Prakashi and Nair, 1982;Carelli and Fahl, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…angulata roots is affected by high solar incidence and temperature. Accordingly,Tanan et al (2019) evaluated variations of NR activity in roots and leaves of P. angulata plants and found that the plants showed peaks of NR activity in the period of highest solar incidence and temperature: the highest activities of NR in leaves were found at 10:00 a.m. and 2:00 p.m., and NR activity in the leaves increased after 4 hours of light incidence.In addition, several works have been developed evaluating the performance of the enzyme nitrate reductase due to its regulatory function and its effect on plant growth and development under differentexperimental conditions; they are based on the hypothesis that plants with high NR enzyme activity may have greater potential to assimilate NO 3 and respond better to nitrogen fertilization (Beevers & Hageman,1969). Viana & Kieh (2010) evaluated the effects of combinations of nitrogen rates on the enzymatic activity of nitrate reductase in leaves of wheat plants and found the highest enzymatic activity for the N rate of 158 mg dm -3 , but from this rate onwards, the NR activity decreased.…”
mentioning
confidence: 99%